2014
DOI: 10.1007/s00253-014-5517-x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus surface antigen as delivery vector can enhance Chlamydia trachomatis MOMP multi-epitope immune response in mice

Abstract: Chlamydia trachomatis is the leading cause of sexually transmitted infections worldwide. There is currently no commercially available vaccine against C. trachomatis. Major outer membrane protein (MOMP) of C. trachomatis is considered to be an ideal candidate for prophylactic vaccine. We designed a MOMP multi-epitope containing T- and B-cell epitope-rich peptides and developed hepatitis B surface antigen (HBsAg) as antigen delivery vehicle. In order to study the immunogenicity and efficacy of the candidate vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…overlapping CTL, HTL and B cell epitopes have the capacity to activate humoral and cellular immune responses simultaneously, iii) linking an adjuvant to the vaccine ensures a long lasting immune response with enhanced immunogenicity, iv) the in vitro antigen expression complications as well as the difficulty of culturing the pathogens can also be avoided [35][36][37][38][39][40][41][42][43]. Designing of multi-epitope vaccines is an emerging area which has already gained importance, and the vaccines designed by this approach, have not only shown in vivo efficacy with protective immunity [44][45][46] but also entered phase-I clinical trials [39,40,47,48].…”
Section: Immune Simulationmentioning
confidence: 99%
“…overlapping CTL, HTL and B cell epitopes have the capacity to activate humoral and cellular immune responses simultaneously, iii) linking an adjuvant to the vaccine ensures a long lasting immune response with enhanced immunogenicity, iv) the in vitro antigen expression complications as well as the difficulty of culturing the pathogens can also be avoided [35][36][37][38][39][40][41][42][43]. Designing of multi-epitope vaccines is an emerging area which has already gained importance, and the vaccines designed by this approach, have not only shown in vivo efficacy with protective immunity [44][45][46] but also entered phase-I clinical trials [39,40,47,48].…”
Section: Immune Simulationmentioning
confidence: 99%
“…Designing of epitope driven vaccine is a modern idea, which is successfully applied in several immunological studies for the development of vaccines [79]. Similarly, the present study is centred on designing of a multi-epitope vaccine because these vaccines have advantages over traditional and single-epitope vaccines due to the following unique features: i) TCRs from various T cell subsets can recognize the multiple MHC Class I and Class II epitopes ; ii) CTL, HTL and B cell epitopes may overlap, thus, it has the capacity to induce humoral and cellular immune responses simultaneously; iii) linking an adjuvant to the vaccine enhances the immunogenicity and provides long lasting immune response; iv) the likelihood of pathological immune responses or adverse effects is lowered because it is less likely to contain unwanted components [29,30,70,[80][81][82][83]]. Further, it has been demonstrated that multi-epitope combined vaccine induce stronger CTL responses compared to those induced by a single-epitope vaccine by enhancing cellular immunity and releasing immune tolerance [29].…”
Section: Discussionmentioning
confidence: 99%
“…50 Ī¼l supernatant were added to another plate supplemented with the substrate cocktail (50 Ī¼l/well), and stopped after 30 min of incubation in the dark to record the optical density at 490 nm. Specific lysis was calculated as follows: % specific lysis = 100 Ɨ [(release in the presence of CTLāˆ’spontaneous release)/(maximal releaseāˆ’spontaneous release)][17, 23]. In all the experiments, the spontaneous release was less than 30% of the maximal release.…”
Section: Methodsmentioning
confidence: 99%
“…The tissues were fixed in formalin, embedded in paraffin, and sectioned 5 Ī¼m/each section. The sections were stained with hematoxylin and eosin (H&E) and were assessed by a pathologist blinded to mouse treatment [23]. …”
Section: Methodsmentioning
confidence: 99%